Information Policies and Higher Education Choices Experimental Evidence from Colombia (2017)
Governments have recently invested in online information systems that provide labor market statistics and financial aid options to help students make higher education choices. This paper uses a randomized controlled trial to study the extent to which this information influences students' understanding of the potential wage premium associated with various college degrees; performance on tests that are key in college admissions; and subsequent decisions about whether and where to enroll in college. We collect data on more than 6,000 students across 115 public schools in Bogota, Colombia. Students in 58 schools were given a 35-minute presentation that provides labor market and funding information: average earning premiums upon completing college, available financial aid options to cover costs, and the importance of test scores for admission and financing. Results indicate that students learn about financial aid but do not change their generally inflated beliefs about earnings associated with college degrees